Effectiveness of aortic balloon occlusion in reducing blood loss during cesarean section in placenta accreta spectrum disorders: a study protocol for a randomized controlled trial - Gauri Bapayeva; Gulzhanat Aimagambetova; Gulzhanat Aimagambetova; Nazira Kadroldinova; Viktor Zemlyanskiy; Kuat Kassymbek; Milan Terzic; Milan Terzic (Frontiers in Medicine)
IntroductionObstetric hemorrhage is one of the leading causes of maternal mortality and morbidity worldwide. One of the major risk factors of obstetric hemorrhage include placenta previa and placenta accreta spectrum (PAS) disorders. The frequency of PAS disorders is increasing worldwide and is accompanied by massive intraoperative bleeding with hemorrhagic shock and increasing rates of cesarean hysterectomy. To decrease the risks of bleeding, various approaches to endovascular balloon occlusion have been tested during the past decade.ObjectivesThis study aimed to evaluate the effectiveness of resuscitative endovascular balloon occlusion of the aorta (REBOA) in reducing blood loss and preserving the reproductive organs during cesarean section. Study design: This will be a prospective randomized controlled trial involving 144 patients in a tertiary care obstetric center in Kazakhstan. The study population will consist of pregnant women who will be admitted for cesarean section due to placenta previa complicated by PAS disorders. The study subjects will be randomly divided into intervention and control groups.ResultsThe results will be analyzed through the measurement of primary (blood loss during cesarean section) and secondary outcomes [occurrence of hysterectomy during cesarean section, blood transfusion volume, duration of surgery, balloon application time, stay in intensive care unit (ICU), neonatal outcomes, complications, and total days of postsurgical hospital stay].ConclusionThe use of REBOA is expected to minimize intraoperative blood loss during cesarean section, decrease the need for transfusion of blood components, reduce the time of surgical intervention, decrease the rate of maternal complications, and reduce the rate of cesarean hysterectomy.